Competency Curriculum Reform: The Experience in the Preparatorias Federales por Cooperacion - Silva Montes, Cesar (Education Policy Analysis Archives, 2015)
In this article, the effects of curriculum reform in Preparatorias Federales por Cooperacion, driven by the Direccion General del Bachillerato, are analyzed. It´s purpose is to reveal how the curriculum competencies, in order to connect school with labor market in the context of globalization and the knowledge society, are inconsistent with the ideal of educated citizens committed to society. The curriculum, as a social construction, represents the ideals of the human beings and society in a certain historical moment. In the case of Ciudad Juarez, the graduate profile seeks to link the Toyotist manufacturing model with the maquiladora industry which demands workers adaptable, flexible and capable to solve problems. The attempt to link the school with the work sphere is a mirage, because the economic crisis, technological development and labor flexibility causes unemployment and precarious working conditions. Another effect of the curriculum is to update teachers in constructivist didactics and certification in competencies, which reduces their teaching autonomy. In addition, teachers will be excluded from the definition of curricular graduate profiles, plans and programs of study, making them a simple executor of external goals. The livelihoods of this analysis are literature and government documents review, additionally of my participation in the task force for the curriculum reform in 2002 and meetings with managers and officials.